Yield improvement of Spinach (Spinacia oleracea L.) in summer culture through use of a new kind of infrared-cutting net. Issue 1 (2nd January 2019) - Fukuoka, Nobuyuki; Murakami, Kenji; Ikoma, Hiroki; Morikawa, Sinya; Suzuki, Toshiyuki; Suzuki, Mami; Murakami, Kenji; Noto, Shinsuke
ABSTRACT: In this study, we examined the covering effect of a new kind of infrared ray (IR)-cutting net to improve the low yield of summer-sown spinach crops in greenhouse. This IR-cutting net gives about 61% transmittance of visible light and approx. 50–54% absorbance of IR from 700 to 2600 nm. The utilisation of IR-cutting net in summer could favour plant growth due to lowering greenhouse temperatures. The globe temperatures when shielded by the IR-cutting net were approx. 6–8ºC lower than without the net, an effect nearly equal to that of a 50% shade net. Although the plant growth was significantly reduced when plants were grown without a net, the crop productivity was intensified more by covering with the IR-cutting net than the 50% shade net. Mean fresh weight and yield for the IR-cutting net treatment was approx. 1.6 and 1.3 times larger, respectively, than for the 50% shade net. Although the photosynthetic capacity of plants grown without a net is suppressed by high temperature, this decreased photosynthetic capacity can be improved by covering with the IR-cutting net. We demonstrated that the IR-cutting net led to successful production of summer-sown spinach from the agrotechnical point of view.